Turbulensi Lingkungan dan Kapasitas Strategi Perusahaan Ritel pada PT Hero Supermarket Tbk: Turbulensi Lingkungan dan Kapasitas Strategi Perusahaan Ritel pada Pt Hero Supermarket Tbk - Taufik Raharjo; Agus Sunarya Sulaeman; Roby Syaiful Ubed (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This study aims to analyze the position of PT Hero Supermarket Tbk's environmental turbulence level, and analyze PT Hero Supermarket Tbk's strategy to optimize the company's performance and sustainability. The research method used is descriptive qualitative, utilizing secondary data from various literature such as books, articles and homepages to access the latest data and information to analyze environmental turbulence and strategies implemented by PT Hero Supermarket Tbk. The Result of this study that PT Hero Supermarket Tbk's environmental turbulence level is at level 4 (Discontinuous) and 5 (Suprising). Considering that PT Hero Supermarket Tbk's turbulence level is at levels 4 and 5, to optimize performance and sustainability the company can use an "entrepreneurial" strategy in the short term, but must start trying to implement a "creative novel" strategy. In addition, management must be able to respond by developing the company to be able to control the environment and create a new environment (market).